2019
DOI: 10.1097/fbp.0000000000000484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-ethylpentylone on locomotor activity and anxiety-like behavior in rats

Abstract: N-ethylpentylone (NEP), a new synthetic cathinone, has been rising to be one of the most popular cathinone derivatives in recent years. However, research on NEP is rather limited. In this study, locomotor stimulation and sensitization, as well as anxiety-like behavior induced by NEP were studied in Sprague-Dawley rats, using the open field and elevated plus maze respectively. Rats were administered NEP (5, 20 or 50 mg/kg, intraperitoneal), with saline as the negative control and methamphetamine (5 mg/kg) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…On the contrary, NEP showed an inverted U-shaped dose-response curve due to the emergence of focused stereotypes such as sniffing and head bobbing at the higher dose tested (Baumann et al, 2018). This inverted U-shaped dose-response curve of the locomotor activity is not unique of NEP, but a common effect of stimulants, since other authors have observed the same effect not only for NEP (Gatch et al, 2019;Li et al, 2019) but also for other novel synthetic cathinones, such as eutylone (Glatfelter et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…On the contrary, NEP showed an inverted U-shaped dose-response curve due to the emergence of focused stereotypes such as sniffing and head bobbing at the higher dose tested (Baumann et al, 2018). This inverted U-shaped dose-response curve of the locomotor activity is not unique of NEP, but a common effect of stimulants, since other authors have observed the same effect not only for NEP (Gatch et al, 2019;Li et al, 2019) but also for other novel synthetic cathinones, such as eutylone (Glatfelter et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Regarding the highest dose tested (30 mg/kg), not only a ceiling effect was observed in the cumulative distance traveled induced by NEB and NEPD administrations (Figure B,C) but an abrupt decreasing slope after a high and initial hyperlocomotion was also observed (Figure B,C). Both events might be explained by the emergence of stereotypes, a common effect when injecting high doses of synthetic cathinones into rodents, which results in reduced hyperlocomotion. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, increased anxiety will result in a preference to stay in the outer edge of the arena. Thus, in our work, the open field test has been used to study the anxiety-like effects of halogen-derivatives of α-PVP as it has already been described for some synthetic cathinones [42,43]. Our results point to an anxiogenic effect induced by the acute administration of 3-F-α-PVP, 4-F-α-PVP, 3-Br-α-PVP, 3-Cl-α-PVP, 4-Clα-PVP, and 3,4-Cl 2 -α-PVP.…”
Section: Discussionmentioning
confidence: 99%